The time-varying long-run rate of unemployment in Colombia - Arango, Luis E.; Posada, Carlos E. (Investigación Económica, 2019)
After the failure of the Phillips curve to explain the simultaneous ocurrence of rising inflation and unemployment, the classical approach to the theory of unemployment and inflation reemerged (see Friedman 1968; Phelps 1967, 1968). Milton Friedman (1968) defined the natural rate of unemployment as the level that would be ground out by the Walrasian system of general equilibrium equations, provided there is imbedded in them the actual structural characteristics of the labor and commodity markets, including market imperfections, stochastic variability in demand and supplies, the cost of gathering information about job vacancies and labor avialabilities, the cost of mobility, and so on.